2021
DOI: 10.1371/journal.pone.0254935
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ utilization and associated factors of preconception care in Africa, a systematic review and meta-analysis

Abstract: Background As the studies show, in every minute in the world, 380 women become pregnant and 190 face unplanned or unwanted pregnancies; 110 experience pregnancy-related complications, and one woman dies from a pregnancy-related cause. Preconception care is one of the proven strategies for the reduction in mortality and decreases the risk of adverse health effects for the woman, fetus, and neonate by optimizing maternal health services and improves woman’s health. Therefore, this study aimed to estimate the poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The findings of our study revealed that 21.6% (95% CI: 18, 25.8) of the respondents utilized preconception care. This finding was in line with studies done in the West Guji Zone (22.3%) ( 34 ), Mekelle (18.2%) ( 27 ), Hosanna Town (19%) ( 35 ), south-east Nigeria (23.4%) ( 36 ), and systematic review and meta-analysis in Africa (18.72%) ( 37 ).…”
Section: Discussionsupporting
confidence: 87%
“…The findings of our study revealed that 21.6% (95% CI: 18, 25.8) of the respondents utilized preconception care. This finding was in line with studies done in the West Guji Zone (22.3%) ( 34 ), Mekelle (18.2%) ( 27 ), Hosanna Town (19%) ( 35 ), south-east Nigeria (23.4%) ( 36 ), and systematic review and meta-analysis in Africa (18.72%) ( 37 ).…”
Section: Discussionsupporting
confidence: 87%
“…Low knowledge of couples of childbearing age is one of the factors associated with service utilization. Couples of childbearing age with low knowledge of preconception health are less likely to take advantage of this service (15). Likewise, women couples of childbearing age with low levels of education are less likely to make visits to preconception care services (14,19).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on women in the West Guji Zone, Southern Ethiopia, found that education level, economic status, level of knowledge, and attitudes of couples of childbearing age in uence the use of preconception care (14). All systematic reviews and meta-analyses in Africa factored in knowledge of preconception care, medical history, and desire to conceive related to the use of preconception care (15). Relatively different results were found in a study conducted on pregnant women attending antenatal care clinics of public health facilities in Hosanna town, southern Ethiopia, in which a history of contraceptive use, poor obstetric history, and low knowledge and counseling about preconception care affected the use of preconception care.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent systematic review and meta-analysis showed that the overall utilisation of preconception care in Africa was low at 18.72%. 11 Similarly, a recent review in sub-Saharan Africa (SSA) found that the pooled utilisation of preconception care was low at 24.05%. 12 Furthermore, a systematic review and meta-analysis in Ethiopia has…”
Section: Introductionmentioning
confidence: 99%